Inquiry-based learning and the pre-requisite for its use in science at school: A meta-analysis - Heindl, Manuela (Journal of pedagogical research, 2019)
The purpose of this meta-analysis was to determine the pre-requisite for and the efficacy of inquiry-based learning to improve academic performance in contrast to traditional lessons. Randomised studies with pre- and post-test design with control and treatment groups were filtered with a priori inclusion criteria and analysed in Review Manager (2014). Out of the results in ERIC 13 studies were found, which show that inquiry-based learning can be more effective when the students and the teachers are well-prepared (Messner, 2009). The results of this meta-analysis of the studies between 2011 and 2017, as well as the theory in the literature, show that there is a positive effect size towards its regular implementation in primary (d= 0.67) and secondary schools (d = 0.81). Therefore, there should be more inquiry-based learning lessons taught in science and in other school subjects and the pre-requisite according to Messner (2009) have an effect of d = 0.88.